1993
DOI: 10.1111/j.1600-051x.1993.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of periodontal tissue destruction at splinted/non‐splinted teeth

Abstract: The aim of the present investigation was to study whether splinting, i.e., immobilisation of teeth, may interfere with the rate of periodontal tissue destruction that can be accomplished by ligature placement and plaque accumulation, 5, 1-year-old, beagle dogs were included in the experiment. The mandibular 2nd and 3rd premolars and the 1st molar on both sides of the mandible were extracted. 2 titanium implants were installed in the sites of 3P and 1M, i.e., in the right quadrant of the mandible. 3 months late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The present investigation demonstrated that in dogs allowed to form plaque, the placement of cotton floss ligatures at the neck of mandibular premolars initiated a process that resulted in (i) the formation of an infiammatory lesion which extended deep into the supracrestal connective tissue, (ii) extensive loss of alveolar bone, and (iii) markedly increased tooth mobility. These findings confirm data from similar experiments in the rat (Rovin et al, 1966), in the ferret (Fischer & Klinge 1994), in the monkey (e.g,, Kennedy & Poison 1973, Poison & Zander 1983, Holt et al 1988 and in the dog (e,g,, Ericsson et al, 1975, 1993 demonstrating that periodontal tissue breakdown in this model is dependent on (i) the mechanical irritation provided by the ligature and (ii) the establishment of a subgingival plaque.…”
Section: Discussionsupporting
confidence: 85%
“…The present investigation demonstrated that in dogs allowed to form plaque, the placement of cotton floss ligatures at the neck of mandibular premolars initiated a process that resulted in (i) the formation of an infiammatory lesion which extended deep into the supracrestal connective tissue, (ii) extensive loss of alveolar bone, and (iii) markedly increased tooth mobility. These findings confirm data from similar experiments in the rat (Rovin et al, 1966), in the ferret (Fischer & Klinge 1994), in the monkey (e.g,, Kennedy & Poison 1973, Poison & Zander 1983, Holt et al 1988 and in the dog (e,g,, Ericsson et al, 1975, 1993 demonstrating that periodontal tissue breakdown in this model is dependent on (i) the mechanical irritation provided by the ligature and (ii) the establishment of a subgingival plaque.…”
Section: Discussionsupporting
confidence: 85%
“…, ; Ericsson et al. ; Pontoriero et al. ) have documented that plaque formation at implant sites results in mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in humans and experiments in animals (e.g. Berglundh et al 1992Berglundh et al , 2004Ericsson et al 1993;Pontoriero et al 1994) have documented that plaque formation at implant sites results in mucositis. In the present study, mucositis (BoP+) occurred in 88% of subjects and in 81% of all implant sites.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animals reported similar periodontal breakdown around teeth regardless of being splinted to implants or not [61, 83, 84]. Pesun et al [85] found that histology of periodontal ligament around teeth connected to implants was similar to control teeth with minimal inflammation and minimal remodeling.…”
Section: Resultsmentioning
confidence: 99%